2022
DOI: 10.3390/catal12070690
|View full text |Cite
|
Sign up to set email alerts
|

Surface Inactivation of Human Coronavirus by MACOMA™ UVA-TiO2 Coupled Photocatalytic Disinfection System

Abstract: There is an immense healthcare challenge and financial pressure due to the COVID-19 pandemic caused by a newly identified human coronavirus, SARS-CoV-2. Effective COVID-19 prevention efforts in healthcare, home, and community settings highlight the need for rapid, efficient, and no-contact SARS-CoV-2 inactivation strategies. Here, we examined the photocatalytic and virucidal activity of the MACOMA™ TiO2 photocatalytic film activated by an UVA-LED-12V-367 nm (MA-717836-1) lamp against the HCoV-OC43, a member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…UV (200–280 nm) irradiation is a potentially effective disinfection method that is widely used for disinfection of surfaces and is able to deactivate different types of viruses including SARS-CoV-2 . Under UV irradiation, RNA absorbs the UV photon which blocks the transcription via the formation of pyrimidine dimers, while absorption of UV radiation by amino acids disturbs the activity and structural function of the proteins . However, the disinfection mechanism of SARS-CoV-2 under UV irradiation is not clear and requires further investigation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…UV (200–280 nm) irradiation is a potentially effective disinfection method that is widely used for disinfection of surfaces and is able to deactivate different types of viruses including SARS-CoV-2 . Under UV irradiation, RNA absorbs the UV photon which blocks the transcription via the formation of pyrimidine dimers, while absorption of UV radiation by amino acids disturbs the activity and structural function of the proteins . However, the disinfection mechanism of SARS-CoV-2 under UV irradiation is not clear and requires further investigation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was suggested that this model could be promising for various air conditioning systems to make free cabin from bacterial and viral infections. Recently Uppal et al 70 proposed TiO 2 photocatalytic coating for virucidal activity against HCoV-OC43 virus which is a member of beta coronavirus family just like SARS CoV-2 under the influence of UV irradiation. It was found that the TiO 2 -coated glass surface exhibited good antiviral response against the virus compared to uncoated glass using T-qPCR and virus infectivity tests.…”
Section: Proposed Approaches For Waste Management Associated With The...mentioning
confidence: 99%
“…The photocatalytic disinfection was explained by observing the virion morphology using transmission electron microscopy (TEM) by detecting damaged viral RNA and proteins as shown in Figure 9a. These nano-photocatalysts are shown to be very promising antiviral coatings for protecting surfaces against the spread of viruses such as COVID-19 [73][74][75]. Recently Uppal et al [74] performed the study of a TiO 2 photocatalytic coating for virucidal activity against the HCoV-OC43 virus which is a member of the beta coronaviruses family just like SARS-CoV-2 under the influence of UV irradiation using T-qPCR and virus infectivity assays.…”
Section: Tio 2 Based Nano-photocatalysts As Potential Antibacterial A...mentioning
confidence: 99%
“…These nano-photocatalysts are shown to be very promising antiviral coatings for protecting surfaces against the spread of viruses such as COVID-19 [73][74][75]. Recently Uppal et al [74] performed the study of a TiO 2 photocatalytic coating for virucidal activity against the HCoV-OC43 virus which is a member of the beta coronaviruses family just like SARS-CoV-2 under the influence of UV irradiation using T-qPCR and virus infectivity assays. It was found that the glass surface coated with TiO 2 exhibited better antiviral response as compared to uncoated glass against the virus.…”
Section: Tio 2 Based Nano-photocatalysts As Potential Antibacterial A...mentioning
confidence: 99%
See 1 more Smart Citation